2010
DOI: 10.1021/ie100115x
|View full text |Cite
|
Sign up to set email alerts
|

The Breadth and Intensity of Supercritical Particle Formation Research with an Emphasis on Publication and Patent Disclosures

Abstract: The drawbacks of the conventional mechanical treatments for particle micronization often resulting in product damage or performance degradation have highlighted the need for alternative particle formation processes. The aim of this study was to shed light on the trends of the scientific studies and innovations in the field of particle formation using supercritical fluids (SCF) in order to observe the progress of science and technology and to satisfy the need for a global view of research activities. The public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 81 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…Microencapsulation is an alternative approach to overcome these drawbacks particularly by masking the unpleasant taste of ingredients and enhancing the stabilityt. Both conventional encapsulation techniques and more advanced approaches such as supercritical antisolvent processes are applied to obtain encapsulated particles ranging from micro-to nanometers [7,8]. Propolis has been encapsulated with different methods but only one study focused on encapsulation of ethanol extract of propolis (EEP) by complex coacervation where soy protein and pectin were used as wall materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation is an alternative approach to overcome these drawbacks particularly by masking the unpleasant taste of ingredients and enhancing the stabilityt. Both conventional encapsulation techniques and more advanced approaches such as supercritical antisolvent processes are applied to obtain encapsulated particles ranging from micro-to nanometers [7,8]. Propolis has been encapsulated with different methods but only one study focused on encapsulation of ethanol extract of propolis (EEP) by complex coacervation where soy protein and pectin were used as wall materials [3].…”
Section: Introductionmentioning
confidence: 99%
“…Later, another study showed a bibliometric analysis of the patents and scientific publications in the laser cladding field from 1985 to 2007 [ 5 ]. In 2010, using supercritical fluids, Yesil-Celiktas and Senyay shed light on the trends of the scientific studies and innovations in the field of particle formation [ 6 ]. One year later, patent bibliometric analysis was used for tracking the R&D behavior in the pharmaceutical industry [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The RESS method occupies one of the leading places in publications and patents devoted to creating nanoparticles using SCF [4]. The continuous flow mode of various modifications of the RESS method is attractive for SCF technologies for its simplicity and low equipment cost.…”
Section: Introductionmentioning
confidence: 99%